Browser Extension Endpoint Security Anti Spyware dan Data Exfiltration Berbasis Rule based Java Script : Rekayasa Keamanan Siber - ricki2114; Bambang Purwanto; Robianto Herdana Sukirno (Pustaka Poltekad, 2026)
The expansion of web based applications has increased browser side security risks, particularly through malicious Java Script exploitation leading to data exfiltration. Conventional endpoint security mechanisms primarily emphasize network-layer monitoring, leaving client side browser activities less protected. This study proposes a browser extension-based endpoint security solution employing a rule based Java Script monitoring approach to detect spyware behavior and prevent unauthorized data transmission. Using the Research and Development (R&D) methodology, the system was designed, implemented and evaluated through controlled attack simulations. The extension monitors DOM access, local storage usage and outbound HTTP/HTTPS requests based on predefined detection rules. Experimental results across ten simulated scenarios demonstrate an 80% detection rate. The findings indicate that rule based client side monitoring offers a lightweight and practical approach to strengthening browser-level endpoint security.